Monitoring Land Use Land Cover Changes and Modelling of Urban Growth Using a Future Land Use Simulation Model (FLUS) in Diyarbakir, Turkey - Cagliyan, Ayse; Dagli, Dundar (Mdpi, 2022)
Land use and land cover (LULC) change corresponds to the greatest transformations that occur on the earth's surface under physical, human and socio-economic geographical conditions. Increasing demand for residential and agricultural lands has been transforming all land classes and this should be investigated in the long term. In this study, we aim to determine LULC change and land use simulation in Diyarbakir with Geographical Information System (GIS) and Remote Sensing (RS) techniques. For this purpose, satellite images from 1984, 2002, and 2020 were classified at different levels by an object-based classification method. Accuracy assessments of the classified images were made and change detection analyses were performed using TerrSet software. The LULC changes were also estimated in different scenarios using a future land use simulation model (FLUS). The results show that natural and semi-natural areas are rapidly disappearing due to urban growth between 1984 and 2020. The results of the land use simulation show that by 2038, while the agricultural, pasture and water bodies will decrease, the built-up areas will increase. It is estimated that the city, which has developed in a west-northwest direction, will expand in the future and grow between Elazig and Sanliurfa Boulevard.
Keywords: land use change; urban growth; urban simulation; FLUS model; Diyarbakir